2014
DOI: 10.1111/all.12553
|View full text |Cite
|
Sign up to set email alerts
|

Detection of nickel and palladium contact hypersensitivity by a flow cytometric lymphocyte proliferation test

Abstract: We established a flow cytometric lymphocyte proliferation test (LPT) for the detection of nickel (Ni) and palladium (Pd) sensitization. Eighty-one consecutive patients with an indication for patch test (PT) were tested by LPT with Ni (NiSO4 ) and Pd (Na2 PdCl4 and PdCl2 ) salts. The imprecision of the LPT was low (coefficient of variation 7.2%). Using PT as a diagnostic reference, the sensitivity and specificity of LPT were 74.4% and 80% for NiSO4 , 74.4% and 78.3% for Na2 PdCl4 , and 57.2% and 85.4% for PdCl2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 17 publications
5
19
1
Order By: Relevance
“…In contrast to the findings of Muris et al, in both groups sodium tetrachloropalladate was more often positive than nickel sulfate. As mentioned above, we noticed similar characteristics in former studies from our department . A reason might be the use of a 3% concentration, as some studies showed a significantly higher number of irritant reactions than with a 2% concentration of tetrachloropalladate …”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In contrast to the findings of Muris et al, in both groups sodium tetrachloropalladate was more often positive than nickel sulfate. As mentioned above, we noticed similar characteristics in former studies from our department . A reason might be the use of a 3% concentration, as some studies showed a significantly higher number of irritant reactions than with a 2% concentration of tetrachloropalladate …”
Section: Discussionsupporting
confidence: 84%
“…However, Pd is not included in the baseline series, making a comparison difficult. The high number of positive test reactions to Pd can partly be explained by cross‐reactivity to Ni, a high proportion of which has been observed in previous studies in our clinic …”
Section: Discussionsupporting
confidence: 55%
“…We found that optimized culture conditions and reference to two Ni stimulatory concentrations (NiSO 4 1 × 10 −5 m and 2.5 × 10 −5 m ) showed the best concordance between patch test and LTT reactivity (88%), with the lowest proportion of non‐specific reactions being seen in patch test‐negative/history‐negative individuals (specificity of 96%). A similar test evaluation against the patch test was reported both by Spoerri et al , using a non‐radioactive flow cytometry assay including patch test‐negative controls, and by Pacheco et al , who introduced a peak SI in controls for calibration. Our approach differs in two respects.…”
Section: Discussionmentioning
confidence: 61%
“…The flow cytometric LPT was performed as previously described, with Candida albicans and toxoid from Clostridium tetani as positive antigens. Cell proliferation in wells without antigen provided baseline proliferation values.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, in the classic LPT, proliferation of uncharacterized lymphocytes is measured by the amount of [ 3 H]thymidine incorporation. To avoid the risk of working with radioactivity and to allow immunophenotypic characterization of proliferating cells, we have recently developed and evaluated a flow cytometric LPT with carboxyfluorescein succinimidyl ester labelling and specific staining of T cell markers for the detection of nickel and palladium sensitization …”
Section: Introductionmentioning
confidence: 99%